2019
DOI: 10.2514/1.a34390
|View full text |Cite
|
Sign up to set email alerts
|

Relative Motion Dynamics in the Restricted Three-Body Problem

Abstract: In this paper, a set of equations for relative motion description in lunar orbits is presented. The local-vertical local-horizon frame is selected to describe the relative dynamics of a chaser approaching a target in lunar orbit, allowing the development of relative guidance and navigation systems for rendezvous and docking. The model considers the Earth and Moon gravitational influence on the two spacecraft, which are assumed to have negligible masses. The proposed equations are intended for the study of rend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 14 publications
(5 reference statements)
0
25
0
Order By: Relevance
“…The aposelene is considered the most feasible area for the docking/berthing. Current literature indicates that as the most likely location, and it has been shown that CR3P equations are sufficiently accurate for the dynamic description of the relative motion [6,21]. In this case, the target has the slowest orbital velocity.…”
Section: Aposelene Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…The aposelene is considered the most feasible area for the docking/berthing. Current literature indicates that as the most likely location, and it has been shown that CR3P equations are sufficiently accurate for the dynamic description of the relative motion [6,21]. In this case, the target has the slowest orbital velocity.…”
Section: Aposelene Approachmentioning
confidence: 99%
“…The close range rendezvous and berthing are assumed to occur during aposelene passage for safety reasons, since the target's velocity is the lowest, this also allows for the simplification of the equations. In this case in fact, the approximation of the primary bodies revolving in circular orbits, (Circular Restricted Three-Body Problem CR3BP assumption) appears appropriate [21]. With this assumption, the number of time-varying parameters in Eq.…”
Section: Relative Translationmentioning
confidence: 99%
“…The NRHO orbit properties, shown in Fig. 1, are given and can be found in [4,7,8], for instance. It has a period of about seven days with 70,000 km as the largest distance from our satellite.…”
Section: Scenario Definitionmentioning
confidence: 99%
“…The key reference frames used in the description of the relative motion are recalled next. They are based on the assumption that the motion of the spacecraft is subjected to the gravitational attraction of both Earth and Moon, and follows the standard definitions in the literature [7,9]. The selected inertial frame is centered at the primaries common center of mass C, with the K̂ unit vector normal to the plane where the primaries revolve, and with the other unit vectors spanning the primaries rotating plane (according to the right-handed rule).…”
Section: Reference Systems and Equations Of Relative Motionmentioning
confidence: 99%
See 1 more Smart Citation